KAJIAN CATU DAYA LISTRIK CADANGAN DI ASRAMA TOWER 2 SEKOLAH TINGGI PENERBANGAN INDONESIA - Ruri Haryati; Hendro Widiarto; Harman Sudjanto (Politeknik Penerbangan Indonesia Curug, 2017)
On this situation, tower 2 dormitory dont have generator set as a back up power supply, so if the main supply from PLN off, all the activity an all infrastructure on dormitory will be stoped and not operate. The process in this study is start from checking all the load on tower 2 dormitory, counting the ideal capacity of the generator set, counting the maximum current of genetator set and ideal position of the generator set. Writer hope this study will be applied in tower 2 dormitory as a solution if the main supply off, so all the activity will be continues.